Gene-Environment Interaction in a Conditional NMDAR-Knockout Model of Schizophrenia - Bygrave, Alexei M.; Masiulis, Simonas; Kullmann, Dimitri M.; Bannerman, David M.; Kätzel, Dennis (Frontiers in Behavioral Neuroscience, 2019)
Interactions between genetic and environmental risk factors take centre stage in the pathology of schizophrenia. We assessed if the stressor of reduced environmental enrichment applied in adulthood provokes deficits in the positive, negative or cognitive symptom domains of schizophrenia in a mouse line modelling NMDA-receptor hypofunction in forebrain inhibitory interneurons (Grin1ΔPpp1r2). We find that Grin1ΔPpp1r2 mice, when group-housed in highly enriched cages, appear largely normal across a wide range of schizophrenia-related behavioural tests. However, they display various short-term memory deficits when exposed to minimal enrichment. This demonstrates that the interaction between risk genes causing NMDA-receptor hypofunction and environmental risk factors may negatively impact cognition later in life.